The impact of Artificial Intelligence on the modern economy (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Artificial Intelligence (AI) is emerging as a transformative force with the potential to reshape the global economic landscape by revolutionizing productivity, innovation, and business operations. The present research paper discusses the impact of AI on the modern economy in five main aspects, including manufacturing, healthcare, finance, retail, and transportation. The study will aim at investigating how the AI technologies are being implemented in these industries, what economical benefits or disruptions they are bringing, and what effect they are producing on the labor markets, GDP growth, and efficiency. The research employs a mixed-methods design that integrates quantitative information (GDP rates, AI investment patterns, and other sector-related performance indicators) and qualitative data obtained through a series of structured interviews with industry professionals and analysts. The results indicate that AI implementation has improved operational efficiency, reduced costs and created new market opportunities to a significant level. One such case is that AI in healthcare has improved the process of diagnostics and reduced the cost of treating patients and AI in manufacturing has automated repetitive tasks, increasing productivity by up to 20 percent. However, the study also singles out the problem of job displacement, skills mismatch, and ethical concerns of data privacy and algorithmic bias. Infrastructural and investment deficit are other barriers experienced in developing economies. The findings show that despite the great economic advantages of AI, its net impact will depend on the establishment of inclusive policies, upskilling the workforce, and responsible innovation.